2004
DOI: 10.1002/jca.20012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of plateletpheresis using Baxter CS 3000 plus and Haemonetics MCS 3P

Abstract: Platelet concentrates made from cell separators are used more frequently due to less donor exposure and leucodepletion. This retrospective study was done to compare plateletpheresis done on two cell separators: Baxter CS 3000 plus and Haemonetics MCS 3p. Plateletpheresis procedures, done from January 1997 to April 2002, were included in the study. One hundred and seven procedures were done on Haemonetics MCS 3p using SDP protocol, 49 procedures were done on Haemonetics MCS 3p using PLP protocol, and 107 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
5
11
0
1
Order By: Relevance
“…Nonetheless, our data do not deviate from the report that no increase of TGF β 1 is detectable in donors' plasma 24 h following plateletpheresis . Indeed, in the present study we have found increases 96 h after donation in accordance with kinetics of sHLA‐I bioactivity as reported in scientific literature . Such increases have become significant 7 days following procedures, but have decreased after 14 days and have reverted to baseline 21 days after each donations.…”
Section: Discussionsupporting
confidence: 76%
“…Nonetheless, our data do not deviate from the report that no increase of TGF β 1 is detectable in donors' plasma 24 h following plateletpheresis . Indeed, in the present study we have found increases 96 h after donation in accordance with kinetics of sHLA‐I bioactivity as reported in scientific literature . Such increases have become significant 7 days following procedures, but have decreased after 14 days and have reverted to baseline 21 days after each donations.…”
Section: Discussionsupporting
confidence: 76%
“…Out of 350 procedures performed at our centre on Baxter CS 3000plus, we found a yield from 3.04-8.8 3 10 11 /unit (3 3 10 11 /unit) in 318 units (90.85%) with the donor pre-procedure platelet count varying between 1.8-4.7 3 10 9 /L. Our observation from northern India is similar to another study from western India [4]. Moreover, in 9.15% of procedures where the yield was <3 3 10 11 /unit, the donor platelet count was 1.5-1.8 3 10 9 /L and in 100% the yield was >2.5 3 10 11 /unit.…”
supporting
confidence: 91%
“…Moreover, in 9.15% of procedures where the yield was <3 3 10 11 /unit, the donor platelet count was 1.5-1.8 3 10 9 /L and in 100% the yield was >2.5 3 10 11 /unit. The authors have not correlated a low platelet yield with the pre-apheresis donor platelet count as the platelet yield is dependent upon the pre-procedure platelet count of the donor, blood volume processed, and efficiency of platelet removal by the cell separator [4]. A statistically higher blood volume was processed using Baxter CS 3000plus as compared to Haemonetics MCS 3p.…”
mentioning
confidence: 99%
“…The MCS+ is being used with the advantage of easy operation and high reliability. Many studies have been made to assess different available apheresis machines regarding procedure time, platelet yield, product quality, adverse effects and other variables (Patel et al , ; Ranganathan, ; Altuntas et al , ; Tendulkar & Rajadhyaksha, ). For example, one study showed that MCS+ could produce almost the same amount of CD34+ compared with the Cosmic Backgoround Explorer (COBE) method, whereas the latter showed more potential (Rock & Sutton, ).…”
mentioning
confidence: 99%